(untitled) (Revista Iberoamericana de Bioética, 2022)
Over the last few decades, medicine has suffered due to an increasing number of ethical complaints and legal procedures. This paper evaluated the reports assessed by the Piauí State Regional Medical Council from 2001 to 2016. 1011 investigations were included and 1073 doctors were involved. There was a significant increase in the number of physicians reported over time (p<0.001). The main complainant was the patient or his or her family/legal representative (54.15%), owing to negligence (31.87%). The gender most frequently reported was male (77.45%). The article discusses factors associated with the growth in the number of reports, due to the distancing of the doctor-patient relationship and the culture of retaliation for medical errors.